Performance evaluation of multihop ad hoc WLANs. - Eshghi, Farshad (IEEE Communications magazine)
Ongoing technological advances in portable devices, coupled with the need for continuous connectivity while mobile, have made ad hoc networks a compelling research and development topic, particularly in a challenging multimedia multihop scenario. The ability of IEEE 802.11's ad hoc mode of operation, as a dominating wireless local area network (WLAN) protocol, to serve multihop networks requires thorough investigation. In this article, through considering crucial real-life physical phenomena and avoiding as many confining assumptions as possible, system performance measures such as delay and packet failure rate are evaluated. As a result, the importance of adequate selection of the system parameters toward performance improvement is underscored. Moreover, the simulation results imply that by complementing through priority provisions, coordination, route reservation, clustering, and optimum channel coding considerations, the IEEE 802.11 medium access control (MAC) protocol can survive in a multihop scenario. The custom simulation environment developed features modularity, comprising traffic generator, mobility, wireless channel, and IEEE 802.11 protocol modules, and is capable of accommodating many more of the physical phenomena involved.